The gravitationally lensed blazar PKS 1830-211 seen by Alma- Determination of the time delay between the lensed images - David, Mariana Alves (My University, 2016)
Abstract PKS1830−211 is a blazar lensed by a foreground galaxy. The alignment of these two objects causes the formation of two distinct compact images embedded in a pseudo- Einstein ring. In this master thesis, we use multi-epoch and multi-frequency data, collected by the Atacama Large Millimeter/submillimeter Array (ALMA) in 2012 and 2014, with the aim of determining the time delay between the two lensed images. These have been resolved in all observations and, by modelling the flux of the North- East image and the flux ratio of both images, the time delay was found to be (28 ± 3) days. This result can be used in future work to better constrain the lens model of the system constituted by the blazar and its foreground galaxy. Furthermore, the physics of the jet was studied by interpretation of the measurements and spectral indices which varied between both periods and were found to be (0.77 ± 0.03) and (0.35 ± 0.10) in 2012 and 2014 respectively.
Keywords: Grundläggande vetenskaper; Astronomi, astrofysik och kosmologi; Basic Sciences; Astronomy, Astrophysics and Cosmology